2014
DOI: 10.1063/1.4896857
|View full text |Cite
|
Sign up to set email alerts
|

The valence band structure of AgxRh1–x alloy nanoparticles

Abstract: The valence band (VB) structures of face-centered-cubic Ag-Rh alloy nanoparticles (NPs), which are known to have excellent hydrogen-storage properties, were investigated using bulk-sensitive hard x-ray photoelectron spectroscopy. The observed VB spectra profiles of the Ag-Rh alloy NPs do not resemble simple linear combinations of the VB spectra of Ag and Rh NPs. The observed VB hybridization was qualitatively reproduced via a first-principles calculation. The electronic structure of the Ag0.5Rh0.5 alloy NPs ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 28 publications
5
36
0
Order By: Relevance
“…For all NPs, the main contribution to the total DOS in the VB region is from degenerated Rh 4 d states (cumulative effect of t 2 g and e g states39), because the photoionization cross-section of Rh 4 d at 6 keV is approximately 6 times that for Cu 3 d 40. The energies of Rh 4 d triplet structure A-C are consistent with previously reported experimental data as well as theoretical calculations41424344. In addition, reported VB data for larger monometallic Rh NPs (12.2 ± 1.6 nm) prepared in a similar manner qualitatively resemble the VB spectrum of bulk Rh41.…”
Section: Resultssupporting
confidence: 89%
“…For all NPs, the main contribution to the total DOS in the VB region is from degenerated Rh 4 d states (cumulative effect of t 2 g and e g states39), because the photoionization cross-section of Rh 4 d at 6 keV is approximately 6 times that for Cu 3 d 40. The energies of Rh 4 d triplet structure A-C are consistent with previously reported experimental data as well as theoretical calculations41424344. In addition, reported VB data for larger monometallic Rh NPs (12.2 ± 1.6 nm) prepared in a similar manner qualitatively resemble the VB spectrum of bulk Rh41.…”
Section: Resultssupporting
confidence: 89%
“…2 (f) and (g) (x ¼ 0.625 and 0.75) the cases with relatively high Ag, the DOS near E F is quite small. the Comparing the DOS's of Ag x Rh 1-x alloy with that of Pd, Ag 0.5 Rh 0.5 shows a high similarity especially at the Fermi edge vicinity as reported in the preceding work [18] while those of Ag 0.125 Rh 0.875 and Ag 0.875 Rh 0.125 are apparently different from that of Pd. We can see that the similarities of other intermediate compositions lie in between.…”
Section: Density Of Statessupporting
confidence: 67%
“…While the bottom edge of the band almost keep constant just under E-E F ¼ À6 eV, the top edge becomes lower with increasing the content of Ag. In the preceding study, the valence band structure of Ag 0.5 Rh 0.5 is carefully investigated on the basis of hard X-ray photoelectron spectroscopy measurements and DFT calculations [18]. The striking similarity of electronic structure of Ag 0.5 Rh 0.5 alloy with Pd in the E-E F range of 0 to À3.5 eV was found.…”
Section: Density Of Statesmentioning
confidence: 98%
See 1 more Smart Citation
“…Surprisingly, we found that the Ag 0.5 Rh 0.5 solid-solution alloy was capable of absorbing hydrogen. The hard X-ray photoelectron spectroscopy (HAXPES) indicated that the electronic structures around the Fermi energy were very similar between Ag 0.5 Rh 0.5 alloy NPs and Pd NPs,[75] indicating that Ag 0.5 Rh 0.5 solid-solution NPs can be considered as ‘artificial Pd’. Such a result was also supported by first principles calculation.…”
Section: Solid-solution Type Pd–ru Npsmentioning
confidence: 99%